Field Test and Numerical Simulation Study of Bearing Characteristics of Combined Post-Grouted Piles for Railway Bridges - Runze Zhang; Zilong Guo; Weiming Gong; Zhihui Wan (Applied Sciences)
Utilizing the results of static load tests using the self-balancing method on two large-diameter bored piles from the Huaiyang Left Line Special Bridge Project of the Lianyungang–Zhenjiang Railway, this study aims to investigate the effect of combined tip-and-side post-grouting on the bearing characteristics of post-grouted piles in railway bridges. The difference in bearing performance between individual piles before and after grouting was evaluated using a comparative analysis. The results show that the bearing capacity of the pile foundations is greatly increased by combined tip-and-side post-grouting. In particular, following grouting, a single pile’s maximum bearing capacity rises from 32.99% to 38.42%. The combined post-grouting produces a compressed grout that enhances the mechanical characteristics of the pile–soil contact, resulting in a significant increase in side resistance all the way along the pile. The combined post-grouting also optimizes the performance of the tip resistance, resulting in a more rapid response as the pile tip displacement increases. Additionally, the combined post-grouting modifies the pile shaft’s load transfer mechanism by increasing the tip resistance’s contribution to the pile foundation’s ultimate bearing capacity and moving the bearing’s center of gravity closer to the pile end.